Developing a Market Orientation. - Deshpande, Professor Rohit (SAGE Publications, 1999)
The Marketing Service Institute has a 38 years history of funding high-profile scholarly research on topics that have managerial significance. MSI's pioneering work on developing a market orientation' has only been available as a series of working papers, is now presented in book form for the first time by Sage Publications. This book demonstrates the importance of market orientation on organizational culture (the shared set of values in putting customer first), on strategy (creating superior value for a firm's customers), and on tactics (the set of cross-functional activities directe.